NKX6.3 Regulates Reactive Oxygen Species Production by Suppressing NF-kB and DNMT1 Activities in Gastric Epithelial Cells - Jung Hwan Yoon (Nature Portfolio, 2017)
Abstract NKX6.3 plays an important role in gastric epithelial differentiation and also acts as a gastric tumor suppressor. The specific aim of this study was to determine whether NKX6.3 contributes to gastric mucosal barrier function by regulating reactive oxygen species (ROS) production. NKX6.3 reduced ROS production and regulated expression of anti-oxidant genes, including Hace1. In addition, NKX6.3 reduced DNMT1 expression and activity by down-regulating NF-kB family gene transcription. Silencing of Hace1 recovered ROS production, whereas knock-down of DNMT1 and NF-kB reduced ROS production and induced Hace1 expression by hypomethylating its promoter region. In addition, NKX6.3 inhibited CagA effects on cell growth, ROS production, and NF-kB and DNMT1 activity. In gastric mucosae and cancers, NKX6.3 and Hace1 expression was significantly reduced. The NKX6.3 expression was positively correlated with Hace1 and Nrf2 genes, but negatively correlated with DNMT1. Hypermethylation of Hace1 gene was observed only in gastric mucosae with H. pylori, atrophy and intestinal metaplasia. Thus, these results suggest that NKX6.3 inhibits ROS production by inducing the expression of Hace1 via down-regulating NF-kB and DNMT1 activity in gastric epithelial cells.